Priapism associated with COVID-19: a pediatric case - Çelebi, Miray Yılmaz; Böncüoğlu, Elif; Düzgöl, Mine; Uçan, Ayşe Başak; Şencan, Arzu; Oral, Akgün; Kara, Aybüke Akaslan (The Turkish Journal of Pediatrics, 2022)
Background. Urological involvement is rare in patients with coronavirus disease 2019 (COVID-19). Priapism, one of the urological involvements, was reported as one of the COVID-19 comorbidities in the elderly male patient group but has rarely been reported in the pediatric age group. Case. Herein, a previously healthy 8-year-old patient with COVID-19-associated priapism, which is rare in children, is presented. Conclusions. During the pandemic, in pediatric cases with priapism of unknown etiology, COVID-19 should be one of the diagnoses to be considered.